2015
DOI: 10.1002/brb3.398
|View full text |Cite
|
Sign up to set email alerts
|

Effectiveness of regionalized systems for stroke and myocardial infarction

Abstract: BackgroundAcute ischemic stroke (AIS) and ST‐segment elevation myocardial infarction (STEMI) are ischemic emergencies. Guidelines recommend care delivery within formally regionalized systems of care at designated centers, with bypass of nearby centers of lesser or no designation. We review the evidence of the effectiveness of regionalized systems in AIS and STEMI.MethodsLiterature was searched using terms corresponding to designation of AIS and STEMI systems and from 2010 to the present. Inclusion criteria inc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
14
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(14 citation statements)
references
References 86 publications
(83 reference statements)
0
14
0
Order By: Relevance
“…The narrow time frame for therapeutic administration, which in the UK and AUS is within 4.5 h of symptom onset and in the USA is within 3 (approved indication) or 4.5 (guidelines) h, is one main factor for low treatment rates. However, improved rtPA treatment rates are possible when internal hospital organisational factors are addressed [9-12], and when regional stroke systems are operationalised to support patients with acute stroke [13-16]. …”
Section: Introductionmentioning
confidence: 99%
“…The narrow time frame for therapeutic administration, which in the UK and AUS is within 4.5 h of symptom onset and in the USA is within 3 (approved indication) or 4.5 (guidelines) h, is one main factor for low treatment rates. However, improved rtPA treatment rates are possible when internal hospital organisational factors are addressed [9-12], and when regional stroke systems are operationalised to support patients with acute stroke [13-16]. …”
Section: Introductionmentioning
confidence: 99%
“…Some of these networks have been proved to represent real life-saving therapies, as the implementation of primary revascularization in ST-elevation myocardial infarction (STEMI) within a well-organized system led to a spectacular reduction in STEMI-related mortality. [1][2][3] In an attempt to make the STEMI networks highly effi- 6 According to this study, fewer women than men presented to the hospital in the first 12 hours after angina onset. Interestingly, the authors also demonstrated that in women from this geographical area, coronary events began more frequently in the morning with atypical symptoms.…”
mentioning
confidence: 88%
“… 8 , 24 ST‐Elevation Myocardial Infarction: STEMI regionalized care started in 2004 when the American College of Cardiology/American Heart Association (ACA/AHA) established “door‐to‐balloon” time targets in STEMI. 25 In 2007, the Mission: Lifeline program was started to provide recognition and accelerate regionalization efforts. 26 The Joint Commission as of 2019 has offered 2 voluntary certifications for STEMI care.…”
Section: Established Systemsmentioning
confidence: 99%